Trends in Women’s Leadership of Oncology Clinical Trials - Waldhorn, Ithai; Dekel, Ayelet; Morozov, Anna; Alon, Elisa Sardas; Stave, Danielle; Tsrooya, Noam Ben; Schlosser, Shir; Markel, Gal; Bomze, David; Meirson, Tomer (Frontiers in Oncology, 2022)
It has been widely reported that women are underrepresented in leadership positions within academic medicine. This study aimed to assess trends in women representation as principal investigators (PIs) in oncology clinical trials and to characterize trends in women’s leadership in such trials conducted between 1999 and 2019. The gender of 39,240 PIs leading clinical trials was determined using the gender prediction software Genderize.io. In total, 11,516 (27.7%) women served as PIs. Over the past 20 years, an annual increase of 0.65% in women PIs was observed. Analysis by geographic distribution revealed higher women representation among PIs in North America and Europe compared to Asia. Industry-funded trials were associated with lower women PI representation than academic-funded trials (31.4% vs. 18.8%, p<0.001). Also, women PIs were found to be underrepresented in late-phase as compared to early-phase studies (27.9%, 25.7%, 21.6%, and 22.4% in phase I, II, III, and IV, respectively; Cochran-Armitage test for trend, p<0.001). Furthermore, an association was found between the PI’s gender and enrolment of female subjects (50% vs. 43% female participants led by women vs men PIs, respectively, p<0.001). Taken together, while the gender gap in women’s leadership in oncology trials has been steadily closing, prominent inequalities remain in non-Western countries, advanced study phases, industry-funded trials and appear to be linked to a gender gap in patient accrual. These observations can serve for the development of strategies to increase women’s representation and to monitor progress toward gender equality in PIs of cancer clinical trials.